Retraction: Coco D, Leanza S. Laparoscopic Cholecystectomy (LC): Toward Zero Error. Open Access Maced J Med Sci. 2020 May 28; 8(F):52-57. https://doi.org/10.3889/oamjms.2020.3791 - Spiroski, Mirko (Open Access Macedonian Journal of Medical Sciences, 2020)
Editor-in-Chief has retracted the article Coco D, Leanza S. Laparoscopic Cholecystectomy (LC): Toward Zero Error. Open Access Maced J Med Sci. 2020 May 28; 8(F):52-57. We received a copy of the letter from Dr Vishal Gupta, MS, MCh, FACS and Dr Gaurav Jain sent to Dr Coco. They draw our attention to the fact that this article has taken most of its material from their review article. We contacted corresponding author and he agreed to retract the published paper. As such, we retract the article from the literature and by guidelines and best editorial practices from the Committee on Publication Ethics. We apologize to our audience about this unfortunate situation.